An Analysis of Two Decades of Educational Technology Publications Who, What and Where - Natividad, Gloria (Lecture Notes in Educational Technology,, 2018)
This book presents a challenging and multi-faceted research project that required state-of-the-art methodological approaches. The project involved analyzing data collected from 10,000 research articles published in ten leading journals in the area of educational technology over 20 years, from January 1994 to December 2014; advanced analytic approaches such as latent semantic analysis (LSA); and expert insights and interpretations of the subject matter. It captures the trends in a number of research streams within the discipline of educational technology and identifies the point in time when a massive change took place. This is a significant achievement given that, in epistemology and philosophy of science, there have always been discussions of paradigm shifts, but researchers have always identified them qualitatively. This is the first work to identify a paradigm shift using rigorous quantitative methods. The analysis procedure involved big data and sophisticated analysis, which supported the identification of clusters at several breakpoints from which the richest set was selected in order to provide the most detailed analysis. This comprehensive analysis also shows what has been published and by whom in those ten top-tier journals. This work makes a highly significant contribution to the field of learning technologies and provides the groundwork and a significant data source for other scholars, both new and experienced, to build on and expand in their work.